Evaluation of School Committee Program in Improving Elementary School Teacher Performance - Udit, Udit; MS, Zulaela; Boeriswaty, Endry (International Conference on Elementary Education, 2020)
The School Committee is an independent body that accommodates the role of the community to improve the quality, equality and efficiency of education management in the education unit. The low level of community participation and the non-optimal role of school committees in contributing to educational performance shows that school committees have not been able to carry out their roles and functions. provide consideration, support and oversee school performance in providing education services. This fact implies the need for school committee program research in analyzing the level of achievement of the objectives of the formation, recruitment, implementation of functions, and program success in improving school performance using the CIPP (Context-Input-Process-Product) research model program evaluation model. The results showed that 70% of school committee members stated that according to procedures, 60% of school committee recruitment stated that they were not in accordance with procedures, 70% of school committee functions were declared not implemented, and 70% of school performance had been improved. The establishment of a School Committee is a legal mandate that must continue to get reinforcement and support from all parties to improve school performance and the quality of education services